Integrasi Nilai Qur’ani dalam Praktik Pertanian: Studi Living Qur’an di Komunitas AgriQuran Bandung - Chodijah, Siti; Ratnasari, Juni (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This research discusses the implementation of Qur'anic values in agricultural practices through a Living Qur'an study in the AgriQuran community in Bandung Regency. AgriQuran is a community that integrates Islamic principles in sustainable agricultural activities to improve farmers' welfare and preserve the environment. This research uses a Participatory Action Research (PAR) approach, which involves the community actively in the research process and transformative action. The results showed that the AgriQuran community implemented various agricultural innovations based on Islamic values, such as the use of organic fertilizers, sustainable land management, crop brotherhood systems, and an economic approach without usury. The main programs include GreenHouse, AgriVisit, Green Alms, and empowering students through AgriPreneur. In addition, this community encourages an Islamic lifestyle for farmers by emphasizing the importance of worship, environmental care, and food security based on local wisdom. These findings confirm that the application of Qur'anic values in agriculture not only increases production yields but also brings positive social and spiritual impacts to the community. Thus, the Living Qur'an-based agricultural model in the AgriQuran community can be an alternative solution for sustainable agriculture in Indonesia.